1998
DOI: 10.1071/ea97145
|View full text |Cite
|
Sign up to set email alerts
|

Mineral disorders in grazing livestock and the usefulness of soil and plant analysis in the assessment of these disorders

Abstract: Summary. This paper briefly describes common mineral disorders affecting livestock at pasture in Australia, their mineral requirements, factors affecting these requirements and laboratory methods of assessing the mineral status of the animal. The benefits and limitations of mineral analyses of soil and pasture samples for the purposes of identifying and preventing mineral disorders of the grazing animal are discussed. Mineral analyses of pasture are of particular value in the identification of the causes of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 85 publications
(80 reference statements)
1
41
0
Order By: Relevance
“…It is well documented that soil ingestion by animals can have a significant effect on trace mineral ingestion, implying that the elements in soil are bioavailable. Judson & McFarlane (1998) pointed out that in ruminants under normal grazing conditions ingested soil can be a source of mineral elements such as Fe, iodine (I) and Mn. Neser et al (1997) found that young calves with a pre-ruminant, that is, a monogastric, digestive system consuming soil high in Mn, developed Mn toxicity owing to the accumulation of Mn in their livers.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that soil ingestion by animals can have a significant effect on trace mineral ingestion, implying that the elements in soil are bioavailable. Judson & McFarlane (1998) pointed out that in ruminants under normal grazing conditions ingested soil can be a source of mineral elements such as Fe, iodine (I) and Mn. Neser et al (1997) found that young calves with a pre-ruminant, that is, a monogastric, digestive system consuming soil high in Mn, developed Mn toxicity owing to the accumulation of Mn in their livers.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, 5-7% of dairy cows are affected by hypocalcaemia at a clinical level and an estimated 66% are affected by hypocalcaemia at a subclinical level (Sanchez 1999). The problem has been reported in other livestock as well as in dairy cows and hypocalcaemia is a problem in ewes lambing in winter and spring in south-eastern Australia (Judson and McFarlane 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the precalving diet can affect the incidence of postcalving hypocalcaemia in dairy cows (Judson and McFarlane 1998) and ewes (Grant et al 1988). Dry dairy cows consuming feed containing an excess of cations [generally potassium (K) and sodium (Na)] over anions [generally chlorine (Cl) and sulfate (SO 4 )], described as a high dietary cation-anion difference (DCAD), have a higher risk of developing postcalving hypocalcaemia than those fed a low DCAD ration .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the Se content of soil that is available to plants has been used to compile maps showing Se deficient areas (Oldfield, 1999). However, most authorities consider soil analyses and classifications to be of limited value for predicting the mineral status of animals (Suttle, 1988;Paynter, 1996;McDowell, 1997: Judson & McFarlane, 1998. According to Judson & McFarlane (1998), conditions conducive to low absorption rates by plants, and thus low pasture Se concentrations, are low soil pH, waterlogging, rainfall above 500 mm per annum and clover-domination of pastures.…”
Section: Introductionmentioning
confidence: 99%
“…However, most authorities consider soil analyses and classifications to be of limited value for predicting the mineral status of animals (Suttle, 1988;Paynter, 1996;McDowell, 1997: Judson & McFarlane, 1998. According to Judson & McFarlane (1998), conditions conducive to low absorption rates by plants, and thus low pasture Se concentrations, are low soil pH, waterlogging, rainfall above 500 mm per annum and clover-domination of pastures. The Se concentration in vegetation has been used to identify areas where grazing animals are at risk of Se deficiency (Judson & McFarlane, 1998;Oldfield, 1999).…”
Section: Introductionmentioning
confidence: 99%